ANALYSIS AND EXPERIMENTAL RESEARCH OF DEPENDENCE BETWEEN NEURAL NETWORKS TRAINING AND TRAINING PARAMETERS SELECTION - Nikita Alekseyevich Lagunov; Oksana Stanislavovna Mezentseva (Вестник Северо-Кавказского федерального университета)
The article offers an analysis of the results obtained from experimental research into the impact that the major parameters in training selection have on the general training capacity and recognition capacity in neural networks; there are also some recommendations offered regarding efficient development of large training selections containing graphic images of object categories.